Potensi dan Strategi Pengembangan Kawasan Minapolitan Kertasari Kabupaten Sumbawa Barat - Nursan, Muhammad; Nabilah, Sharfina; Sari, Ni Made Wirastika (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2020)
The development of the fisheries and marine sector absolutely must be done to increase the production and competitiveness of fisheries and marine products. The Government of Indonesia has established several areas as minapolitan areas, one of which is West Sumbawa Regency as a minapolitan area for seaweed development. Besides seaweed, the minapolitan area has many other potentials that can be developed to improve the competitiveness and added value of the minapolitan area. Therefore, the purpose of this research is to find out the potential of the Minapolitan Area, analyze the internal and external factors of the Minapolitan Area, and formulating the development strategy of the West Sumbawa Regency Minapolitan Area. This research was conducted from October to December 2020, in Labuhan Kertasari Village, Taliwang District, West Sumbawa Regency, which was selected by purposive sampling. The data used include primary data from the interview results of respondents and secondary data from several related agencies. Analysis of the data used is descriptive analysis and SWOT analysis. The results showed that the West Sumbawa Regency minapolitan area apart from being a seaweed development area also has other potentials such as capture fisheries, marine and inland aquaculture, tourism (small islands, beaches, seaweed education), agricultural food crops, plantations, and animal husbandry. West Sumbawa Regency Minapolitan area development strategy, is a SO (Strengthness-Opportunity) strategy, which is a strategy that utilizes the strengths to seize opportunities or aggressive strategies which include Encouraging investment in the Minapolitan area, Diversifying fishery and agricultural processed products, Increasing development and optimizing use facilities and infrastructure of production, processing and marketing activities of agricultural products in a broad sense and tourism, increasing the potential of agriculture and fisheries and tourism in order to expand employment opportunities and facilitate and accelerate licensing and investment service rules.